2011
DOI: 10.1118/1.3669488
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ultrasound elevation beamwidth artifacts for prostate brachytherapy needle insertion

Abstract: The authors found properly adjusting the TRUS imaging settings to lower the ultrasound gain and power effectively minimized the appearance of elevation beamwidth artifacts and in turn reduced the localization errors of the needle tip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Due to the limitation of ultrasound imaging, system and random error in stepper unit, and imaging artifacts, the catheter tip may be defined proximally or distally as much as 4 mm from its actual location. 27,28 As a result, all the dwell positions in the catheter will be offset by that distance, yielding significant dosimetry discrepancy. 25 When near the urethra, catheter track definition error can cause significant miscalculation of urethral dose, potentially yielding significant toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limitation of ultrasound imaging, system and random error in stepper unit, and imaging artifacts, the catheter tip may be defined proximally or distally as much as 4 mm from its actual location. 27,28 As a result, all the dwell positions in the catheter will be offset by that distance, yielding significant dosimetry discrepancy. 25 When near the urethra, catheter track definition error can cause significant miscalculation of urethral dose, potentially yielding significant toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Further, lower US system gain settings (−15 dB compared to 15 dB) reduced intraobserver variations. Peikari et al found needle localization variations of 0.5–4 mm, depending on needle position with respect to the US fields and settings of gain and power [111]. The influence of geometric uncertainties on dosimetry was evaluated in a model-based simulation [112].…”
Section: Uncertainties At the Patient Levelmentioning
confidence: 99%
“…During the prostate brachytherapy procedure, the needles are inserted into the prostate perpendicular to the transverse ultrasound beam and as such there can be errors in needle tip localisation and seed placement, as well as side lobes that can cause further issues with localisation. Peikari et al2012 [32] descried a Wire-Bridge test phantom that allows for elevation beamwidth measurements to examine the uncertainties associated with localisation. In a study by Sandhu et al 2010 [26], the improvements of tissue harmonic imagining over B-mode imagining for the application of ultrasound guided prostate brachytherapy were investigated for a number of the system parameters resolution, geometric accuracy, depth of penetration, dead zone, signal-to-noise ratio and tissue-toclutter ratio, to compare the two modes using an in house test phantom made from homogenized milk based Tissue mimicking material.…”
Section: Test Phantomsmentioning
confidence: 99%